Macroids from mixed siliciclastic-carbonate high-frequency sequences of the Agrio Formation (Lower Cretaceous), Neuquén Basin: Palaeoecological and palaeoenvironmental constraints - Caratelli, Martina (2021)
Fil: Caratelli, Martina. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.